The Role of Artificial Lakes Located in Forests in the Context of Small Retention, Biodiversity and Climatic Changes—Evidence From Southern Poland - Rafał Starzak; Anna Cieplok; Robert Czerniawski; Aneta Spyra (Ecology and Evolution)
ABSTRACT Drought has an effect on hydrologic conditions and water quality under climate change. Small water retention in forests is one of the priority investment programs implemented in recent years, supported by the European Union. This study aimed to assess the ecological conditions of forest lakes using macrophytes and benthos organisms diversity as an ecological indicator of ecosystem conditions under climatic changes. The study was carried out in forest artificial lakes serving as surface water retention in the context of biodiversity in climatic changes and its role in the retention of water. Despite systematic maintenance activities, a long period of lake existence significantly determines the natural biological processes occurring in lakes and riparian habitats. The analysis showed low values of salinity indicators and the concentration of nitrogen and phosphorus. The pH ranged from 6.2 to 7.6; showing slightly acidic conditions or within the limits of neutral. The model of plant associations showed the occurrence of 24 species of plants within nine plant assemblages in the Phragmitetea and Potametea classes of associations (Biocenotic index 1.007–1.692). Despite human activities, lake condition, as assessed by the ESMI index or the biocenotic diversity indices, is good (0.416–0.648). Climate change, expressed by an increase in the frequency of dry years, creates a situation of changes in filling lakes with water, which, taking into account their small depth, results in dynamically changing conditions for the development of phytolittoral. Along with the phytolittoral changes, benthos communities change, their density and the number of taxa also fluctuate. It should be assumed that with ongoing climate change, these phenomena will probably intensify, which will lead to changes in entire ecosystems at plant and animal levels.